Uporządkuj jednomian
a)(-4)•2•(-3⅛)•⅕
b)(-0,1)•x•10xy²
c)(-a)•6x²•(-5y)•(-0,4)
d)½•×•×•×•(-2y)•(-y)•(-y)
e)½ababababab•(-2)
f)(-1)•(-1)•(-1)•xyxy•(-1)
g)(-3)²•(-3)•a²bb•(-3)
h)6mm²•⅓m³•(-2)•n

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-07T16:12:02+02:00
A)(-4)•2•(-3⅛)•⅕ =-8 x (-²⁵/₈) x ¹/₅ =5
b)(-0,1)•x•10xy² = - x²y²
c)(-a)•6x²•(-5y)•(-0,4) =(-a)•6x²• 2 = -12x²a
d)½•×•×•×•(-2y)•(-y)•(-y) = -x³y³
e)½ababababab•(-2) = - ab⁵
f)(-1)•(-1)•(-1)•xyxy•(-1) = x²y²
g)(-3)²•(-3)•a²bb•(-3) = (-3)⁴a²b²
h)6mm²•⅓m³•(-2)•n = - 4m⁶n



1 5 1